2023
DOI: 10.1007/s00417-023-06180-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the distribution of intra-retinal hyper-reflective foci and the progression of intermediate age-related macular degeneration

Abstract: Purpose To assess the relationship between the distribution of intra-retinal hyper-reflective foci (IHRF) on optical coherence tomography (OCT) and progression of intermediate age-related macular degeneration (iAMD) over 2 years. Methods Cirrus OCT volumes of the macula of subjects enrolled in the Amish Eye Study with 2 years of follow-up were evaluated for the presence of iAMD and IHRF at baseline. The IHRF were counted in a series of 5 sequential en face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The methodology for generating these slabs and quantitatively analyzing IHRF has been detailed in prior reports. 20,22,23 In brief, the procedure includes the following steps: 1) identi cation of the presence of IHRF on structural OCT B-scans (identi ed as well-circumscribed hyperre ective lesions ≥ 3 pixels in size, located within the neurosensory retina); 2) generation of 5 equidistant en-face slabs generated from the mid-retina (each representing 20% of the retinal thickness between the RPE and ILM with the inner surface of the slab following the ILM contour and the outer surface following the RPE contour, using the offset and range function); 3) thresholding and binarization of slabs with ImageJ (version 1.50; National Institutes of Health, Bethesda, MD; available at http://rsb.info.nih.gov/ij/index.html); 24 4) manual removal of other hyper-re ective artifacts surrounding the IHRF (drusen, subretinal drusenoid deposits, blood vessels etc); and nally, 5) automatic quanti cation (using 'analyze particles' function in Image J) of IHRF (number) from each retinal slab thus generated. This procedure was followed for each eye at baseline and at the 24-month follow up (Fig.…”
Section: Oct Analysis Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology for generating these slabs and quantitatively analyzing IHRF has been detailed in prior reports. 20,22,23 In brief, the procedure includes the following steps: 1) identi cation of the presence of IHRF on structural OCT B-scans (identi ed as well-circumscribed hyperre ective lesions ≥ 3 pixels in size, located within the neurosensory retina); 2) generation of 5 equidistant en-face slabs generated from the mid-retina (each representing 20% of the retinal thickness between the RPE and ILM with the inner surface of the slab following the ILM contour and the outer surface following the RPE contour, using the offset and range function); 3) thresholding and binarization of slabs with ImageJ (version 1.50; National Institutes of Health, Bethesda, MD; available at http://rsb.info.nih.gov/ij/index.html); 24 4) manual removal of other hyper-re ective artifacts surrounding the IHRF (drusen, subretinal drusenoid deposits, blood vessels etc); and nally, 5) automatic quanti cation (using 'analyze particles' function in Image J) of IHRF (number) from each retinal slab thus generated. This procedure was followed for each eye at baseline and at the 24-month follow up (Fig.…”
Section: Oct Analysis Protocolmentioning
confidence: 99%
“…16,17 In a recent study, we identi ed that IHRF present in the outer retina, and in particular the outer nuclear layer, were most strongly associated with the risk for progression to late-stage AMD, though IHRF may be identi ed in more inner layers as well. 20 Given the differential risk for progression, we speculated that IHRF present in the more inner retinal layers may differ in their source compared to outer retinal IHRF, but this requires further histopathologic correlation.…”
Section: Introductionmentioning
confidence: 99%
“…The methodology for generating these slabs and quantitatively analyzing IHRF has been detailed in prior reports. 20 , 22 , 23 In brief, the procedure includes the following steps: 1) identification of the presence of IHRF on structural OCT B-scans (identified as well-circumscribed hyperreflective lesions ≥ 3 pixels in size, located within the neurosensory retina); 2) generation of 5 equidistant en-face slabs generated from the mid-retina (each representing 20% of the retinal thickness between the RPE and ILM with the inner surface of the slab following the ILM contour and the outer surface following the RPE contour, using the offset and range function); 3) thresholding and binarization of slabs with ImageJ (version 1.50; National Institutes of Health, Bethesda, MD; available at http://rsb.info.nih.gov/ij/index.html ); 24 4) manual removal of other hyper-reflective artifacts surrounding the IHRF (drusen, subretinal drusenoid deposits, blood vessels etc); and finally, 5) automatic quantification (using ‘analyze particles’ function in Image J) of IHRF (number) from each retinal slab thus generated. This procedure was followed for each eye at baseline and at the 24-month follow up ( Fig.…”
Section: Oct Analysis Protocolmentioning
confidence: 99%
“… 16 , 17 In a recent study, we identified that IHRF present in the outer retina, and in particular the outer nuclear layer, were most strongly associated with the risk for progression to late-stage AMD, though IHRF may be identified in more inner layers as well. 20 Given the differential risk for progression, we speculated that IHRF present in the more inner retinal layers may differ in their source compared to outer retinal IHRF, but this requires further histopathologic correlation.…”
Section: Introductionmentioning
confidence: 99%